Perancangan Sistem Informasi Kursus Komputer dengan Metode Rapid Application Development (RAD) pada LKP Graha Kreatif - Alfi Ardiansyah; Haidar Ali Fakhri; Yayan Wahyudi; Saprudin (CV. Multi Kreasi Media, 2025)
This study aims to design a web-based computer course information system at LKP Graha Kreatif as a solution to the problem of manually distributed course registration information. Using the Rapid Application Development (RAD) method, the system was developed quickly and iteratively to meet the institution’s functional needs. Data collection included observation, interviews, and literature review. The system was implemented using the Laravel framework and tested using Black Box Testing. The results show that the designed system improved the effectiveness of information dissemination and simplified the registration process. This system also provides easier access to training information, supporting the institution’s mission to enhance the digital skills of rural communities.